Thematic orders and the comprehension of subject-extracted relative clauses in Mandarin Chinese - Lin, Chien-Jer C. (Frontiers in Psychology, 2015)
This study investigates the comprehension of three kinds of subject-extracted relative clauses (SRs) in Mandarin Chinese: standard SRs, relative clauses involving the disposal ba construction (‘disposal SRs’), and relative clauses involving the long passive bei constructions (‘passive SRs’). In a self-paced reading experiment, the regions before the relativizer (where the sentential fragments are temporarily ambiguous) showed reading patterns consistent with expectation-based incremental processing: standard SRs (with the highest constructional frequency and the least complex syntactic structure) were processed faster than the other two variants. However, in the regions after the relativizer and the head noun (where the existence of a relative clause is unambiguously indicated), a top-down global effect of thematic ordering was observed: passive SRs (whose thematic role order conforms to the canonical thematic order of Chinese) were read faster than both the standard SRs and the disposal SRs. Taken together, these results suggest that two expectation-based processing factors are involved in the comprehension of Chinese relative clauses, including both the structural probabilities of pre-relativizer constituents and the overall surface thematic orders in the relative clauses.